Pendidikan dan Pelatihan Bantuan Hidup Dasar pada Komunitas Lifeguard di Lokasi Wisata Pantai Cermin - Muhammad Jalaluddin Assuyuthi Chalil; Irfan Hamdani (Universitas Muhammadiyah Sumatera Utara, 2018)
Pantai Cermin Kanan Village is one of the villages in Pantai Cermin Subdistrict, Serdang Bedagai Regency, North Sumatra Province, located on the east coast of Sumatra Island. Because of this location, the Pantai Cermin Kanan Village has long been recognized by the community as a beautiful beach tourism destination and is visited every weekend and other holidays. The local government has sought to advance the coastal tourism industry in this village by building good access to tourist sites, and equally important is establishing the Pantai Cermin Puskesmas as the Regional Technical Implementation Unit (UPTD) of the Tourism Health Center. Based on these data, training is needed that aims to increase the knowledge and ability to conduct Basic Life Assistance (BHD) for the